Pengkajian Kegiatan Strategis Kerukunan Hidup Beragama Di Daerah Khusus (DKI) Jakarta: An Analysis of Strategic Activities for Religious Harmony in the Special Capital Region (DKI) of Jakarta - Miftah Arifin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2003)
Despite government programs promoting interreligious harmony, social unrest and conflicts with ethnic, religious, racial, and intergroup dimensions persist in Indonesia, particularly in DKI Jakarta. Drawing on Talcott Parsons' theory of religion as a system of reference values, this study examines whether officially implemented reconciliation activities have been effective in achieving social stability. The research aims to evaluate the pattern of harmony development in Jakarta, identify factors that support or inhibit it, and analyze past religious conflicts and their resolutions. Using a qualitative descriptive method, data were collected through purposive sampling, including interviews with religious and community leaders and Department of Religious Affairs officials, alongside document analysis of print and electronic media. The findings reveal that dominant conflict triggers are not purely religious but are primarily political and economic, such as land disputes, parking rights, uneven social assistance, and unregulated religious celebrations. The Ketapang tragedy exemplifies how non-religious triggers can escalate into religious violence. The study concludes that harmony programs lack coordination and are often treated reactively. Recommendations include increasing the quality and quantity of religious instructors, establishing continuous and simultaneous programs, and involving the private sector and state-owned enterprises in sustaining interreligious harmony initiatives. Meskipun program pemerintah untuk meningkatkan kerukunan umat beragama telah berjalan, konflik sosial bernuansa suku, agama, ras, dan antargolongan masih terjadi di Indonesia, khususnya DKI Jakarta. Mengacu pada teori Talcott Parsons tentang agama sebagai sistem acuan nilai, penelitian ini mengkaji efektivitas program rekonsiliasi yang telah dilaksanakan pemerintah dalam mencapai stabilitas sosial. Penelitian ini bertujuan mengevaluasi pola pembinaan kerukunan di Jakarta, faktor pendukung dan penghambatnya, serta menganalisis konflik keagamaan yang pernah terjadi. Metode deskriptif kualitatif digunakan dengan teknik purposive sampling melalui wawancara bersama tokoh agama, tokoh masyarakat, dan pejabat Departemen Agama, serta analisis dokumen media cetak dan elektronik. Hasil penelitian menunjukkan bahwa pemicu dominan konflik bukanlah faktor agama semata, melainkan faktor politik dan ekonomi seperti rebutan lahan, parkir, bantuan sosial terselubung, dan perayaan tradisi keagamaan yang kurang memperhatikan umat lain. Tragedi Ketapang menjadi contoh bagaimana faktor non-agama memicu kekerasan bernuansa agama. Kesimpulannya, program kerukunan masih kurang koordinasi dan bersifat reaktif. Rekomendasi mencakup peningkatan kualitas dan kuantitas penyuluh agama, program berkelanjutan, serta keterlibatan swasta dan BUMN dalam upaya kerukunan beragama.